1988
DOI: 10.1159/000199739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atropine on Intestinal Phase of Pancreatic Secretion in Man

Abstract: The effect of atropine on prestimulatory and Lundh-meal-stimulated pancreatic secretion and on plasma cholecystokinin (CCK) levels has been studied in 20 human volunteers. Prestimulatory secretion was lowered by infusion of atropine. From 10 to 30 min after ingestion of the Lundh meal, atropine had no effect on secretion. From 30 to 120 min, the stimulated enzyme secretion was reduced by 90% during infusion of atropine. Plasma CCK levels were not altered by atropine. Similar results were obtained when the test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Unfortunately, in that study, the CCK preparation used was impure and there were no determinations of plasma CCK made in their investigation, therefore, no assessment of physiological relevance could be made. More recently we (5) and others (6,7) have shown that, in humans, CCK infusion that produced plasma CCK levels similar to those seen postprandially stimulated pancreatic secretion by an atropine-sensitive pathway. These observations suggest that in both humans and experimental animals cholinergic neural pathways rather than pancreatic acini represent the primary targets in which CCK acts to stimulate pancreatic enzyme secretion.…”
Section: Discussionmentioning
confidence: 65%
“…Unfortunately, in that study, the CCK preparation used was impure and there were no determinations of plasma CCK made in their investigation, therefore, no assessment of physiological relevance could be made. More recently we (5) and others (6,7) have shown that, in humans, CCK infusion that produced plasma CCK levels similar to those seen postprandially stimulated pancreatic secretion by an atropine-sensitive pathway. These observations suggest that in both humans and experimental animals cholinergic neural pathways rather than pancreatic acini represent the primary targets in which CCK acts to stimulate pancreatic enzyme secretion.…”
Section: Discussionmentioning
confidence: 65%
“…1) after protein administration, loxiglumide did not alter C-peptide responses or estimated insulin secretion rates. C-peptide can be used to accu rately estimate insulin secretion in vivo [24,29,30], It should be noted that, as described pre viously [31], with the intraduodenal nutrient stimulation used, rather high plasma CCK concentrations were found in comparison to those values usually found after orally in gested meals, and that 'normal' postprandial CCK concentrations (approximately 3-8 pmol/1) [21,32] are even less likely to have an influence on insulin secretion.…”
Section: Discussionmentioning
confidence: 99%
“…Both found that the secretory re sponse to a liquid lest meal averaged 50 60% of maximal capacity. Data from our own laboratory have shown that oral intake of a liquid lest meal produces a comparable response to that obtained by perfusing the same meal into the duodenum [17], Perfusion of individual nutrients to the duodenum induces different quantities of enzymes. Carbohydrates have little effect, amino acids an inter mediate effect, and fat causes maximal enzyme output [18], Di Magno and Layer [19] demonstrated that the secretory response of the pancreas depends on when one eats during the interdigestive cycle.…”
Section: Intestinal Phasementioning
confidence: 91%